Methodological Bases of Personnel Policy Formation in the Context of Innovative Development of the Region - Gavrylov, M.; Zerkina, O. (Економічний вісник Донбасу, 2015)
The article discusses methodological basis of personnel policy formation in the context of innovative development of the region. It was found out that establishment and implementation of the state personnel policy,as well as regional and municipal personnel policy, faces a number of difficulties. The components of the concept of regional personnel policy were identified including goals and objectives, mechanisms, principles and strategy. The conceptual basis of mechanism of personnel policy of the region was developed. Conducted studies revealed a number of factors and conditions of external and internal environment, which significantly affects the content and mechanism of implementation of personnel policies. Two groups of regional and sectoral regulations were identified, which must be used in the regional personnel policy for innovative development of the region. The first group helps to determine the perspective of formation and training of innovative personnel and the second group determines the ways of distribution and involvement of personnel. В статті викладено методологічні засади формування кадрової політики в контексті інноваційного розвитку регіону. З’ясовано, що створення і особливо реалізація державної, а також регіональної і муніципальної кадрової політики відчуває на собі ряд складнощів. Виявлено складові концепції регіональної кадрової політики, що включають цілі та завдання, механізм, принципи, стратегію. Викладено концептуальні засади механізму формування кадрової політики регіону. Проведені дослідження виявили ряд факторів і умов зовнішнього і внутрішнього середовища, які суттєвим чином впливають на зміст і механізм реалізації кадрової політики. Визначено дві групи регіональних та галузевих нормативів, які необхідно використовувати при розробці регіональної кадрової політики інноваційного розвитку регіону. Перша дозволяє визначити перспективу у формуванні та підготовці інноваційних кадрів, а друга орієнтири, що характеризують розподіл і використання кадрів. В статье изложены методологические основы формирования кадровой политики в контексте инновационного развития региона. Выяснено, что создание и реализация государственной, а также региональной и муниципальной кадровой политики испытывает на себе ряд сложностей. Выявлены составляющие концепции региональной кадровой политики, включающие цели и задачи, механизм, принципы, стратегию. Изложены концептуальные основы механизма формирования кадровой политики региона. Проведенные исследования выявили ряд факторов и условий внешней и внутренней среды, которые существенным образом влияют на содержание и механизм реализации кадровой политики. Определены две группы региональных и отраслевых нормативов, которые необходимо использовать при разработке региональной кадровой политики инновационного развития региона. Первая группа позволяет определить перспективу в формировании и подготовке инновационных кадров, а вторая ориентиры, характеризующие распределение и использование кадров.